Targeting Multidrug Resistance With Antimicrobial Peptide-Decorated Nanoparticles and Polymers - Maleki Dizaj, Solmaz; Salatin, Sara; Khezri, Khadijeh; Lee, Jyh-Yeuan; Lotfipour, Farzaneh (Frontiers in Microbiology, 2022)
As a category of small peptides frequently found in nature, antimicrobial peptides (AMPs) constitute a major part of the innate immune system of various organisms. Antimicrobial peptides feature various inhibitory effects against fungi, bacteria, viruses, and parasites. Due to the increasing concerns of antibiotic resistance among microorganisms, development of antimicrobial peptides is an emerging tool as a favorable applicability prospect in food, medicine, aquaculture, animal husbandry, and agriculture. This review presents the latest research progress made in the field of antimicrobial peptides, such as their action mechanism, classification, application status, design techniques, as well as a review on decoration of nanoparticles and polymers with antimicrobial peptides that are used in treating multidrug resistance. Lastly, we will highlight recent progress in antiviral peptides to treat emerging viral diseases (e.g., anti-coronavirus peptides) and discuss the outlook of AMP applications.